What is polykoiranie? Aristotle and Aristarchus on Il. 2, 204 - Pontani, Filippomaria (Hyperboreus, 2013)
Both Aristotle and Aristarchus felt uneasy about Odysseus’ praise of monarchy (and disparagement of polykoiranie) in Iliad 2, 203–205: the Stagirite tried to give a suitable philosophical explanation of the passage in his Politics, while the Alexandrian philologist (perhaps in the wake of Aristotle’s doubts) decided tout court to transpose the lines. The present paper tries to follow the reasons and forms of this debate down to the imperial age.